THE EXISTENCE OF INDONESIAN WOMEN IN WOOP.ID AS AN ONLINE PORTAL MEDIA INFORMATION - Noviana Sari (Metacommunication: Journal of Communication Studies, 2019)
The impact of current Digital Era and the influx of various Popular cultures is one reason why women began to show their existence in online media. The digital age makes women and society as a whole find a lot of conveniences, one of which is finding information, news or articles. However, nowadays women are attached to a variety of negative opinions in online media such as pornography objects and sexism issues, but with the presence of a number of special websites around women as if they have more value than sexism but have a positive space in online media. The phenomenon of women's interrelation and the internet is interesting to observe because the internet has its own way of opening new spaces for women to interact those penetrate distance, space, and time. Women move into a market icon that has spectacular value in the world of marketing. Women are considered great beings who can balance between social life, family, carrier, entrepreneurs and various interesting hobbies simultaneously. By analyzing the contents of the text in the media and dissecting articles on the woop.id website that represent women in general and broad in a more concise portion of the lives of women who are active and dynamic in a portal. Acculturation of pop culture and conventional culture Fashion & Beauty, Health, Wedding, Love & Sex and other representations of how many parts of a woman positive action on the internet, not just being a cyberporn, sexual harassment, kidnapping, behavior narcissistic, and consumptive cultural targets. The existence of this website seems to be the starting point for all negative women's imagery in online media and helps accelerate women's empowerment in Indonesia.